Investigating the Role of Charge Transfer in Eco-Friendly Coffee Waste-Based Carbon Dots Coupled to ZnBi-Layered Double Hydroxide Heterojunction for Visible-Light Catalytic Activity - Muhammad Irshad Khan ,; Ramza Akram,; Saddam Hussain,; Imam Hussain,; Muhammad Tariq Asif,; Masab Saeed,; Maqsood ur Rehman, (Dialogue Social Science Review (DSSR), 2025)
The current research focuses on the combined impacts of CDs derived from coffee waste incorporated with ZnBi-LDH structures for the photocatalytic degradation of organic contaminants using visible light. The synthesised CDs going through a hydrothermal process displayed fairly good optical properties and the surface modifications provided a conducive environment to charge transfer and good light absorption within the visible light region. From structural characterizations such as XRD, TEM, and FTIR analyses, it was evidenced that CDs were well incorporated into ZnBi-LDH, and the photocatalytic activity was significantly enhanced due to increased surface area and interfacial charge transfer efficiency. UV-Visible study confirmed the reduction of band gap and eradication of electron-hole recombination in CDs(2%)-ZnBi-LDH hybrid with an excellent degradation capability of 91% for 2,4-dichlorophenoxyacetic acid under visible light. Additional mechanistic studies – scavenger experiments – revealed that photogenerated holes were the most reactive species, with SUP and •OH radicals contribute to the overall process. Stability tests confirmed the possibility of multiple reuse, with the efficiency rate being 94.5% after four runs. These discoveries justify the role of coffee waste valorization in the development of efficient photocatalytic materials for environmental remediation applications, and open up a new avenue in the development of green and sustainable technologies for pollutant degradation